A Novel STATCOM Model for Dynamic Power System Simulations - Castro, Luis M.; Acha, Enrique; Fuerte-Esquivel, Claudio R. (IEEE transactions on power systems, 2013)
This paper introduces an advanced model of the STATCOM suitable for steady-state and dynamic simulations of large-scale power systems. It allows for a comprehensive representation of the STATCOM's AC and DC circuits-this is in contrast to current practice where the STATCOM is represented using an equivalent variable voltage source which is not amenable to a proper representation of its DC circuit. The new STATCOM model comprises a voltage source converter (VSC) in series with an LTC transformer. The former is represented by a complex tap-changing transformer whose primary and secondary windings would correspond, in a notional sense, to the VSC's AC and DC buses, respectively. The magnitude and phase angle of the complex tap changer correspond to the amplitude modulation index and the phase shift that would exist in a PWM inverter to enable either reactive power generation or absorption purely by electronic processing of the voltage and current waveforms within the VSC. The numerical technique employed to solve the STATCOM model is the Newton-Raphson method for both operating regimes, the steady-state and the dynamic-state. The latter involves discretization of the STATCOMs and synchronous generators differential equations so that the nonlinear algebraic equations and the discretized differential equations are linearized around a base operating point and assembled together in a unified frame-of-reference for robust iterative solutions.